Triglyceride Glucose-Body Mass Index and Risk of Incident Type 2 Diabetes Mellitus in Japanese People With Normal Glycemic Level: A Population-Based Longitudinal Cohort Study - Song, Bei; Zhao, Xiaofang; Yao, Tianci; Lu, Weilin; Zhang, Hao; Liu, Ting; Liu, Chengyun; Wang, Kun (Frontiers in Endocrinology, 2022)
Background: It has been proved that triglyceride glucose-body mass index (TyG-BMI) is a readily available and clinically significant indicator of insulin resistance (IR). Nevertheless, the association between TyG-BMI and incident Type 2 diabetes mellitus (T2DM) remains uncertain. The purpose of this study was to study the relationship between TyG-BMI and T2DM and explore the predictive characteristics of TyG-BMI. Methods: Our study was conducted as a longitudinal cohort study. 8430 men and 7034 women were enrolled and analyzed. They were both non-diabetic subjects with normal glycemic levels. Follow-up lasted for 13 years, from 1994 to 2016. In order to make the number of TyG-BMI in each group similar, the subjects were divided into four groups with 3866 subjects in each group. Results: During the 13-year follow-up period, 373 subjects were diagnosed with incident T2DM. Our multivariate Cox regression analysis revealed that TyG-BMI was an independent predictor of incident T2DM. In addition, our research identified four specific groups, the young people (18-45 years old), women, the non-hypertensive population and non-drinkers were at significantly higher risk of developing TyG-BMI-related diabetes (P-interaction< 0.05). Conclusions: Our longitudinal cohort study demonstrated that the predictive value of TyG-BMI was higher than TyG index and BMI in Japanese with normal glycemic levels. In clinical practice, the TyG-BMI will be helpful for the early detection and treatment of incident T2DM in the Japanese population.